Analysis Of The Implementation Of Clay Media In Improving The Creativity Of 5–6-Year-Old Children At Bintang Nahdlatul Wathan Rempek Paud In The 2024/2025 Academic Year - Baeti, Hijjul; Marzoan, Marzoan; Ramzi, Muhajirin (JUPE : Jurnal Pendidikan Mandala, 2025)
Abstract. This study aims to analyze the steps taken by teachers in implementing clay media to enhance the creativity of children aged 5–6 years during the teaching and learning process at PAUD Bintang Nahdlatu Wathan in the 2024/2025 academic year. The research was conducted at PAUD Bintang Nahdlatu Wathan, Group B, with a total of 18 students.This study is a descriptive qualitative research using a case study approach. Data collection techniques included observation, interviews, and documentation. Information was gathered from the homeroom teacher, the principal, and the students. The data analysis techniques used in this study are: (1) data condensation, (2) data display, and (3) conclusion drawing.The results of the study indicate that the implementation of clay media was carried out through four main stages: (1) preparation, (2) opening activities, (3) core activities, and (4) closing activities, supported by methods such as play, demonstration, experimentation, question and answer, and storytelling. The teacher acted as a facilitator, guiding the children through the learning process.The use of clay media proved effective in developing children's creativity. Through direct engagement with concrete media, children were able to explore, imagine, and dare to try without fear of making mistakes. In addition to fostering creativity, the media also supported the development of fine motor skills, cognitive abilities, emotional growth, and social skills. These findings indicate that clay-based learning not only stimulates creativity but also provides holistic benefits for early childhood development.